Reporting Black Lives Matters: Deaths in custody journalism in Australia - Bonita Mason (Asia Pacific Network, 2020)
George Floyd’s death at the knee of USA police sparked protests and renewed reporting of Indigenous deaths in custody in Australia. As the 30th anniversary of the release of the final report of the Australian Royal Commission into Aboriginal Deaths in Custody approaches, it is timely to update Wendy Bacon’s 2005 research on deaths in custody journalism. While most deaths in custody continue to pass in judicial and media silence, this article, written from a white journalism academic’s perspective, includes instances of in-depth reporting since 2005, journalism that meets the Royal Commission’s observation that journalism can contribute to justice for Aboriginal people when it places deaths in custody in their social and moral contexts. It also includes mini-case study of the news coverage of Mr Ward’s 2008 death, which demonstrates the relationship between governmental or judicial processes and announcements and patterns of coverage. It also notes the effect that First Nations journalists are having on the prevalence, perspectives and depth of deaths in custody journalism. Information and resources are provided for journalists and journalism students to more effectively report Indigenous deaths in custody, include Indigenous voices in their stories, and to better understand trauma and take care of themselves, their sources and their communities